An Evaluation of Causality, Severity, and Preventability of Adverse Drug Reactions Reported by Undergraduate Medical Students in a Tertiary Care Hospital - Mohammad Y. Bhat; Samina Farhat; Urfan Nabi (Universitas Padjadjaran, Indonesia, 2022)
Adverse drug reactions (ADRs) have become a major clinical problem that causes mortality and morbidity, besides causing an additional burden on the total cost of patient treatment worldwide. Therefore, this study aimed to assess ADRs’ causality, severity, and prevent- ability and sensitize undergraduate medical students to reduce underreporting cases. A ret- rospective observational study in J&K tertiary teaching hospital in India. We conducted the study after sensitizing the students about pharmacovigilance and guiding them to submit individual case safety reports (ICSRs) of ADRs during their clinical stages. The study was conducted for ten months, from May 2020 to February 2021, as a part of their internal assess- ment, followed by evaluating the data using simple descriptive statistics. We analyzed a total of 124 reports over the stipulated time. The most common ADRs reported were related to skin and appendages, and antibiotics accounted for a maximum number of cases. Causality assessment showed that most ADRs were possible (61.1%) and probable (38.8%). Severity and preventability assessment revealed that most reported ADRs were moderate (67.9%) and mild (32.0%), while most ADRs were preventable, with only 30.0% of them not preventable. Students reported valuable and clinically relevant ADRs. This study will foster the culture of reporting and analyzing the impact of ADRs among undergraduate students. Furthermore, since most ADRs in this study were preventable, managing such ADRs through therapeutic intervention would benefit better patient care.